2011
DOI: 10.1002/nau.20999
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil for the treatment of lower urinary tract symptoms secondary to benign prostatic hyperplasia: Pathophysiology and mechanism(s) of action

Abstract: The pathophysiology of male LUTS is complex and not completely understood. LUTS may occur independently of BPH or secondary to BPH but in both cases involve obstructive or irritative mechanisms with substantial pathophysiological overlap. While the precise mechanism remains unclear, inhibition of PDE5 seems to have an effect on several pathways that may impact LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
213
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(227 citation statements)
references
References 127 publications
9
213
0
5
Order By: Relevance
“…Tadalafil has its therapeutic effects through beneficial actions on smooth muscle relaxation, smooth muscle and endothelial cell proliferation, nerve activity and tissue perfusion. 89 Significant improvement in IPSS after PDE5-inhibitor therapy compared with placebo was reported in all clinical studies with the magnitude of IPSS improvement comparable with those reported in previous a-blocker studies. Interestingly, none of the studies showed a significant effect of PDE5-I on peak urinary flow rate.…”
Section: Luts and Ed: Effects On Clinical Managementsupporting
confidence: 82%
“…Tadalafil has its therapeutic effects through beneficial actions on smooth muscle relaxation, smooth muscle and endothelial cell proliferation, nerve activity and tissue perfusion. 89 Significant improvement in IPSS after PDE5-inhibitor therapy compared with placebo was reported in all clinical studies with the magnitude of IPSS improvement comparable with those reported in previous a-blocker studies. Interestingly, none of the studies showed a significant effect of PDE5-I on peak urinary flow rate.…”
Section: Luts and Ed: Effects On Clinical Managementsupporting
confidence: 82%
“…Bladder ischemia is caused by reduced bladder blood flow associated with aging, arteriosclerosis and BOO. Recent reports indicated a strong relationship of LUTS/BPH with metabolic syndrome and erectile dysfunction (ED) [22,23], and many studies demonstrated that PDE5i, agents used for the treatment of ED, also improved LUTS in patients with BPH [11][12][13]. The results of these studies implicate that LUTS/BPH are partially attributed to disturbance in the NO/cGMP pathway caused by reduced bladder blood flow, and that PDE5i could improve LUTS/BPH by activating the NO/cGMP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These basic studies are translated into clinical urology and PDE5i is Matsumoto S, et al, Effect of PDE3i treatment on female rat obstructed bladder -5 -used for treating male LUTS [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[19] While LUTS is ultimately a multifactorial and multidimensional problem, similarities between the pathophysiological mechanisms of LUTS and ED include the nitric oxide-cyclic guanosine monophosphate (NO/ cGMP) pathway, RhoA/Rho-kinase signaling, pelvic ischemia, and autonomic adrenergic over activity. [19,20] These similarities may explain why PDE5 inhibitors such as tadalafil and sildenafil are successfully utilized in the treatment of BPH-related LUTS. Taken alone, PDE5 inhibitors reduce the International Prostate Score Symptoms scores by nearly three points compared with the scores using a placebo and demonstrate moderate synergy when taken in combination with α-blockers.…”
Section: Avanafilmentioning
confidence: 99%
“…Taken alone, PDE5 inhibitors reduce the International Prostate Score Symptoms scores by nearly three points compared with the scores using a placebo and demonstrate moderate synergy when taken in combination with α-blockers. [19,20] There is currently a lack of objectivity, however, pertaining to the effects of PDE5 inhibitors (i.e., tadalafil) on other quantifiable variables such as Q max . [19,21] The AUA does not include PDE5 inhibitors in its clinical guidelines for LUTS, but the European Association of Urology lists the class of medications under "new emerging drugs" for the treatment of male LUTS.…”
Section: Avanafilmentioning
confidence: 99%